Elections in Africa: a data handbook - Nohlen, Dieter (Oxford Univ. Press, 1999)
This is a country-by-country study of African nations, providing a comparative introduction on elections and electoral systems. Data is presented in a sytematic manner, allowing for both historical and cross-national comparisons.